LncRNA-SRA1 Suppresses Osteosarcoma Cell Proliferation While Promoting Cell Apoptosis. (19th July 2019) - Guo, Wen; Jiang, Haitao; Li, Haijun; Li, Fang; Yu, Qing; Liu, Yu; Jiang, Weiwei; Zhang, Ming
Objective: Osteosarcoma is a common malignant bone tumor that is frequently found in the long bones of children and adolescents. The aim of this study is to examine long noncoding RNA-steroid receptor RNA activator 1 expression in osteosarcoma to explore the biological function of long noncoding RNA steroid receptor RNA activator 1 on proliferation, migration, and invasion along with apoptosis and its regulatory mechanism, which would facilitate the early diagnosis and targeted therapy of osteosarcoma. Methods: First, microarray analysis was applied to determine the expression of long noncoding RNAs in osteosarcoma tissues and paired normal tissues. Then, quantitative real-time polymerase chain reaction was utilized to validate microarray findings. Next, osteosarcoma cancerous cell lines SJSA-1 and U2OS were transfected with pcDNA3.1-SRA1 or pCMV-sh-SRA1 to increase or decrease steroid receptor RNA activator 1 expression levels, and microRNA-208a inhibitors, mimic to investigate the effects of microRNA-208a on osteosarcoma as well as the regulatory relation between long noncoding RNA steroid receptor RNA activator 1 and microRNA-208a. Cell proliferation was evaluated through Cell Counting Kit-8 and colony formation assays. Flow cytometry analysis was conducted to evaluate the apoptosis ratio. The migration and invasion abilities were measured using wound-healing and transwell assays. Results: Long noncoding RNA-steroid receptor RNA activator 1 expression was downregulated in osteosarcoma tissues and cells compared with that in corresponding normal tissues, whereas microRNA-208a expression was upregulated in osteosarcoma tissues. Moreover, the restoration of long noncoding RNA steroid receptor RNA activator 1 inhibited cell proliferation, and upregulation of long noncoding RNA steroid receptor RNA activator 1 restrained cell migration and invasion but boosted the apoptosis rate in osteosarcoma cells. In addition, long noncoding RNA steroid receptor RNA activator 1 targeting microRNA-208a was involved in the progression of osteosarcoma. Furthermore, upregulating microRNA-208a exerted similar roles of silencing long noncoding RNA steroid receptor RNA activator 1 in cell apoptosis, proliferation, migration, and invasion, which were reversed by enhancing the expression of long noncoding RNA steroid receptor RNA activator 1. Conclusions: In our study, long noncoding RNA steroid receptor RNA activator 1 played an antitumor role in osteosarcoma as it reduced cell migration, invasion, and proliferation, but facilitated cell apoptosis via sponging microRNA-208a, which could be regarded as a potential therapeutic target of osteosarcoma treatment.